Scientific Frontier Mapping of Circular Entrepreneurship: Emerging Themes and Knowledge Dynamics (2015–2025) - Judijanto, Loso (Eastasouth Institute, 2025)
This study aims to map the scientific frontier of circular entrepreneurship by examining its emerging themes, intellectual foundations, and evolving knowledge dynamics over the period 2015–2025. Using a science-mapping approach based on bibliometric data retrieved from the Scopus database, the study applies co-citation analysis, bibliographic coupling, keyword co-occurrence, and network visualizations with VOSviewer to uncover the structural and conceptual development of the field. The findings reveal that circular entrepreneurship is anchored by the concept of the circular economy and increasingly integrated with entrepreneurship, innovation, and sustainability-oriented business models. Thematic clustering indicates four dominant research streams: sustainable and social entrepreneurship, entrepreneurial innovation and firm dynamics, environmental management and impact, and circular business models with stakeholder engagement. Temporal and density analyses further demonstrate a shift from conceptual and normative discussions toward applied, ecosystem-based, and impact-oriented research. The study provides a comprehensive overview of how circular entrepreneurship has matured into an interdisciplinary and globally connected research domain, offering a structured foundation for future theoretical development, empirical investigation, and policy-oriented research.